Reflective Faculty Evaluation: Enhancing Teaching and Determining Faculty Effectiveness - Centra, John A. (Jossey-Bass, 1993)
This volume on college and university faculty evaluation presents the latest findings, approaches, and issues with an emphasis on careful reflection for all involved. Chapter One discusses the diverse responsibilities of college faculty and the role evaluation can play in faculty improvement. Chapter Two presents a brief history of teaching methods and summarizes the various approaches used in college classrooms. Chapter Three presents the history of student evaluation of faculty performance and related research. Chapter Four discusses the benefits of using student evaluations for formative and summative purposes and concludes with 12 guidelines for the proper use of student evaluations. Chapter Five addresses the potential of various kinds of self-reports including the teaching portfolio. Chapter Six describes how some institutions have successfully involved colleagues in formative and summative evaluation. Chapter Seven discusses the conceptions of research and scholarship and the relationship between a faculty member's performance as a researcher and as a teacher. Chapter Eight looks at the current legal climate and the need to protect individual rights when evaluation systems are designed. Chapter Nine includes a brief discussion of the use of measures of student learning in formative and summative evaluation. It also provides criteria for judging the quality of teacher-made examinations and other assessment practices.
Keywords: évaluation de l'enseignement